2022
DOI: 10.21203/rs.3.rs-2387106/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of and relevant factors for depression and anxiety symptoms among pregnant women on the eastern seaboard of China in the post-COVID-19 era

Abstract: Background Antenatal depression and anxiety symptoms may have negative consequences for both mothers and offspring, and upward trends in the prevalence of these symptoms were especially apparent during the COVID-19 epidemic. The purpose of this study was to evaluate the prevalence of and relevant factors influencing depressive and anxiety symptoms in Chinese pregnant women in the post-COVID-19 era. Methods We conducted an online survey of 1,963 pregnant women in Jiangsu Province, using a cross-sectional desi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…7 A study in China showed that the prevalence of prenatal depression, anxiety, and depression combined with anxiety were 25.2%, 27.9%, and 18.6%, respectively. 8 Inappropriate coping with these negative emotions not only affects the health status of the pregnant woman, but also poses a risk to the health of the offspring, 9 the relationship of the couple, 10 and the functioning of the family. 11 Research has shown that lack of family support and spouse support are risk factors for prenatal depression and anxiety, 12,13 while good family relationships are protective factors for prenatal depression.…”
Section: Introductionmentioning
confidence: 99%
“…7 A study in China showed that the prevalence of prenatal depression, anxiety, and depression combined with anxiety were 25.2%, 27.9%, and 18.6%, respectively. 8 Inappropriate coping with these negative emotions not only affects the health status of the pregnant woman, but also poses a risk to the health of the offspring, 9 the relationship of the couple, 10 and the functioning of the family. 11 Research has shown that lack of family support and spouse support are risk factors for prenatal depression and anxiety, 12,13 while good family relationships are protective factors for prenatal depression.…”
Section: Introductionmentioning
confidence: 99%